Residents' Perceptions of Passive Design Responding to Climate Change in Simple Houses in Depok, West Java, Indonesia - Anisa, Anisa; Jundullah Afgani, Jundi; Lissimia, Finta (The Indonesian Forestry Certification Cooperation, 2024)
Since the last few years, environmental issues related to global warming and increasing earth surface temperatures have had an influence on various fields. This environmental issue also affects the micro and macro climate. Architecturally, design can respond to changes in microclimate with passive design and active design. Passive design has long been applied to vernacular architecture, namely responding to local conditions in buildings. Meanwhile, active design is related to the latest technology and developments, such as energy-saving technology, as well as the use of natural elements as energy sources. This research uses quantitative methods. Primary data was collected using a questionnaire to determine the tendency of residents' perceptions of passive design. The analysis of this research is descriptive statistics, based on the answers of 35 respondents who live in simple houses in Depok, West Java, Indonesia. The research results showed that respondents' tendency towards passive design was shown in several things, namely: additional elements of the building at the front (canopy) can reduce heat and create shadow areas, the location and size of openings can support natural lighting and ventilation. Openings can be doors, windows, grilles, rosters and other elements. The existence of open space at the front and back of the house can reduce heat and cool the microclimate.